2011
DOI: 10.1016/j.cub.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Control in Sensing Chromosome Biorientation by the Aurora B Kinase

Abstract: Maintenance of genome stability during cell division depends on establishing correct attachments between chromosomes and spindle microtubules. Correct, bi-oriented attachments are stabilized, while incorrect attachments are selectively destabilized. This process relies largely on increased phosphorylation of kinetochore substrates of Aurora B kinase at misaligned versus aligned kinetochores. Current models explain this differential phosphorylation by spatial changes in the position of substrates relative to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 39 publications
7
138
2
Order By: Relevance
“…This array of cargo proteins implies the existence in mitosis of a complex but coordinated regulation to ensure chromosome segregation. We and others have shown that the mitotic kinases, PLK1 and Aurora B, form a feedback loop to control MCAK, a microtubule regulator (20,26,27). As established here, acetyl regulation of the K220-SxIP interaction is another layer of fidelity control in mitotic chromosome plasticity.…”
Section: Discussionmentioning
confidence: 91%
“…This array of cargo proteins implies the existence in mitosis of a complex but coordinated regulation to ensure chromosome segregation. We and others have shown that the mitotic kinases, PLK1 and Aurora B, form a feedback loop to control MCAK, a microtubule regulator (20,26,27). As established here, acetyl regulation of the K220-SxIP interaction is another layer of fidelity control in mitotic chromosome plasticity.…”
Section: Discussionmentioning
confidence: 91%
“…The following primary antibodies were used in immunofluorescence: CREST autoimmune serum (Antibodies Incorporated; #15-234; 1:30), anti-AURKC (Bethyl #A400-023A-BL1217; 1:30) antibody, anti-Ī±-tubulinAlexa-Fluor-488 conjugate (Life Technologies #322588; 1:100), and antipericentrin (BD Biosciences #611814; 1:100), anti-Ī³-tubulin (Sigma #T6557; 1:100), anti-AURKA (Bethyl A300-072A; 1:30), anti-pAURKA (Cell Signaling #3079S; 1:30), anti-pINCENP (gift of Michael Lampson, University of Pennsylvania, Philadelphia, PA; 1:1000; Salimian et al, 2011) and anti-survivin (Cell Signaling Technology #2808S; 1:500) antibodies.…”
Section: Antibodiesmentioning
confidence: 99%
“…Including a spatially variable phosphatase concentration and also localisation of phosphatases to kinetochores could provide a much more sophisticated view of the opposing action of kinases and phosphatases at kinetochores. Aurora B is found at higher concentrations at improper kinetochore-microtubule attachments [40,95,105] . Therefore, a natural extension of a model which includes kinetochore-microtubule attachments would be to incorporate a dependence of the centromeric binding dynamics on the kinetochore-microtubule attachment state.…”
Section: The Models May Be Extended To Include Other Componentsmentioning
confidence: 99%